1997
DOI: 10.1557/proc-481-509
|View full text |Cite
|
Sign up to set email alerts
|

Initial Phase Formation During Interdiffusion

Abstract: In multiphase materials systems involved in coatings, composites or multilayered structures, diffusion treatments often results in the development of intermediate phases at the reaction interfaces. While diffusional growth of phases has received much attention, the initial phase evolution involves a nucleation stage as well. The development of metastable phases during solid state interdiffusion demonstrates that the nucleation reaction can be controlling in some cases. For alloy systems with extensive solubili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The control of interface reactions between reinforcement materials and matrix is a significantly important issue which should be considered together with the individual material properties in a successful composite. 2 In this paper, the intermetallic nickel aluminide alloys is utilized as a binder for TiC-based cermets. It is found that changing the C/Ti ratio in TiC x can optimize the adhesion and phase evolution in the composite materials fabricated by the metallic melt impregnation method.…”
Section: Introductionmentioning
confidence: 99%
“…The control of interface reactions between reinforcement materials and matrix is a significantly important issue which should be considered together with the individual material properties in a successful composite. 2 In this paper, the intermetallic nickel aluminide alloys is utilized as a binder for TiC-based cermets. It is found that changing the C/Ti ratio in TiC x can optimize the adhesion and phase evolution in the composite materials fabricated by the metallic melt impregnation method.…”
Section: Introductionmentioning
confidence: 99%